Water Resources Analysis: An Approach based on Agent-Based Modeling - Farias, Giovani; Leitzke, Bruna; Born, Míriam; Aguiar, Marilton; Adamatti, Diana (Revista de Informática Teórica e Aplicada, 2020)
The paper aims to present a river basin modeling using GAMA platform for water resources analysis. Currently, several models based on multi-agent systems are used for natural resources management and they present satisfactory results for this type of scenario. GAMA is agents based and widely used in this context with several studies already published. In this study, the Sa ̃o Gonc ̧alo and Lagoa Mirim basins were considered from georeferenced data. In the modeling, regions, and rivers are agents on the system where rivers water can flow among neighbors regions.